2014
DOI: 10.1371/journal.pone.0099186
|View full text |Cite|
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-1 as a Prognostic Marker in Patients with Acute Ischemic Stroke

Abstract: ObjectiveInsulin-like growth factor-1 (IGF-1) has been associated with cardiovascular risk factors and atherosclerosis. The aim of the present study was to evaluate the prognostic value of IGF-1 levels in patients with acute ischemic stroke (AIS).MethodsAll patients with first-ever AIS from August 1, 2012 to August 31, 2013 were recruited to participate in the study. Clinical data were collected. The National Institutes of Health Stroke Scale (NIHSS) score was assessed on admission blinded to serum IGF-1 level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 34 publications
(36 reference statements)
1
38
0
2
Order By: Relevance
“…Extensive numbers of clinical studies have shown that lower IGF-1 levels significantly increase the risk of stroke and higher IGF-1 levels are associated with improved stroke outcomes, suggesting the circulating IGF-1 level may be used as a predictive value for ischemic stroke outcome (De Smedt et al 2011; Dong et al 2014; Tang et al 2014) and post-stroke IGF-1 treatment may be beneficial to both sexes. However, a recent study using miRNA that regulate IGF-1 found sex differences in the efficacy of this treatment.…”
Section: Sex Differences In Treatment Efficacy In Preclinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive numbers of clinical studies have shown that lower IGF-1 levels significantly increase the risk of stroke and higher IGF-1 levels are associated with improved stroke outcomes, suggesting the circulating IGF-1 level may be used as a predictive value for ischemic stroke outcome (De Smedt et al 2011; Dong et al 2014; Tang et al 2014) and post-stroke IGF-1 treatment may be beneficial to both sexes. However, a recent study using miRNA that regulate IGF-1 found sex differences in the efficacy of this treatment.…”
Section: Sex Differences In Treatment Efficacy In Preclinical Studiesmentioning
confidence: 99%
“…It has been well established clinically that serum IGF-1 levels are positively correlated with stroke outcome. Many clinical studies have shown that lower IGF-1 levels significantly increase the risk of stroke and that higher IGF-1 levels are associated with improved stroke outcomes, suggesting that the circulating IGF-1 level may be used as a predictive value for ischemic stroke outcome (De Smedt et al, 2011;Dong et al, 2014;Tang et al, 2014) and that poststroke IGF-1 treatment may be beneficial for both sexes. However, using miRNA that regulate IGF-1, Selvamani and colleagues (2012) showed sex differences in the efficacy of this treatment and showed that intracerebroventricular anti-Let7f injection is effective only in intact females and not in males or ovariectomized females, suggesting that this miRNA action may be influenced by the hormonal milieu (Selvamani et al, 2012).…”
Section: Cell Survival Effector: Insulin-like Growth Factor-1mentioning
confidence: 99%
“…[3][4][5] Previous studies regarding stroke patients have suggested that low IGF-1 levels in the circulation are related with higher stroke severity, poor outcome, and less rates of survival after stroke. [6][7][8][9] De Smedt et al (2011) suggested that high serum IGF-I levels after the onset of ischemic stroke are associated with neurological recovery and a better functional outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of IGF-1 with simultaneously low levels of IGFBP-3 allow for greater amounts of free, unbound IGF-1 in circulation, which, in turn, elicits IGF-1 to trigger cascades in neuroprotective pathways. In individuals with stroke, many studies have agreed that high baseline levels of IGF-1 in circulation, measured once within the first few weeks of stroke, are linked to lower stroke severity and greater rates of survival at one-month post stroke (611). …”
Section: Introductionmentioning
confidence: 99%